Approaching 18% efficiency of ternary organic photovoltaics with wide bandgap polymer donor and well compatible Y6 : Y6-1O as acceptor. Issue 8 (31st December 2020) - Ma, Xiaoling; Zeng, Anping; Gao, Jinhua; Hu, Zhenghao; Xu, Chunyu; Son, Jae Hoon; Jeong, Sang Young; Zhang, Caixia; Li, Mengyang; Wang, Kai; Yan, He; Ma, Zaifei; et al.
Abstract: A series of ternary organic photovoltaics (OPVs) are fabricated with one wide bandgap polymer D18-Cl as donor, and well compatible Y6 and Y6-1O as acceptor. The open-circuit-voltage ( VOC ) of ternary OPVs is monotonously increased along with the incorporation of Y6-1O, indicating that the alloy state should be formed between Y6 and Y6-1O due to their excellent compatibility. The energy loss can be minimized by incorporating Y6-1O, leading to the VOC improvement of ternary OPVs. By finely adjusting the Y6-1O content, a power conversion efficiency of 17.91% is achieved in the optimal ternary OPVs with 30 wt% Y6-1O in acceptors, resulting from synchronously improved short-circuit-current density ( JSC ) of 25.87 mA cm −2, fill factor (FF) of 76.92% and VOC of 0.900 V in comparison with those of D18-Cl : Y6 binary OPVs. The JSC and FF improvement of ternary OPVs should be ascribed to comprehensively optimal photon harvesting, exciton dissociation and charge transport in ternary active layers. The more efficient charge separation and transport process in ternary active layers can be confirmed by the magneto-photocurrent and impedance spectroscopy experimental results, respectively. This work provides new insight into constructing highly efficient ternary OPVs with well compatible Y6 and its derivative as acceptor. Abstract : By employing the well compatible Y6 : Y6-1O as acceptor and wide bandgap polymer D18-Cl as donor, the PCE of 17.91% is achieved in optimized ternary OPVs, resulting from the simultaneously improved JSC, FF and VOC .